Childhood asthma may be a consequence of vitamin D deficiency - Litonjua, Augusto A. (2009)
PURPOSE OF REVIEW: Vitamin D deficiency has been rediscovered as a public health problem worldwide. It has been postulated that vitamin D deficiency may explain a portion of the asthma epidemic. The purpose of this review is to present the evidence for a role of vitamin D in asthma. RECENT FINDINGS: Both animal models and studies in human fetal tissues show that vitamin D plays a role in fetal lung growth and maturation. Epidemiologic studies have also suggested that higher prenatal vitamin D intakes have a protective role against wheezing illnesses in young children. Vitamin D may protect against wheezing illnesses through its role in upregulating antimicrobial proteins or through its multiple immune effects. In addition, vitamin D may play a therapeutic role in steroid resistant asthmatics, and lower vitamin D levels have recently been associated with higher risks for asthma exacerbations. SUMMARY: Improving vitamin D status holds promise in primary prevention of asthma, in decreasing exacerbations of disease, and in treating steroid resistance. However, the appropriate level of circulating vitamin D for optimal immune functioning remains unclear. Because vitamin D deficiency is prevalent even in sun-replete areas, clinical trials are needed to definitively answer questions about the role of vitamin D in asthma.